Leucocyte Ascorbic Acid Levels and Vitamin C Intake in Older People. Issue 5784 (13th November 1971) - Milne, J. S.; Lonergan, M. E.; Williamson, J.; Moore, F. M. L.; McMaster, R.; Percy, N.
Abstract : Leucocyte ascorbic acid (L.A.A.) levels and vitamin C intake were measured in a random sample of men and women aged 62-94 years. L.A.A. distributions are positively skewed but log normal. L.A.A. mean values show no age difference in men but are significantly lower in older women. The mean value for all women (23·88μg/10 8 cells) is significantly higher than that for all men (18·11 μg/10 8 cells). L.A.A. values are significantly higher in both sexes in the six months July to December. Vitamin C intake distributions are positively skewed but not improved by log transformation. No significant age or sex differences were found except that a significantly greater proportion of men over than of those under 70 years have intakes less than 30 mg daily. Mean intake is significantly higher in men but not in women in the six months April to September, though in both sexes a significantly greater proportion have intakes less than 30 mg daily in October to March compared with April to September. Fifty per cent. of men and 58% of women have intakes less than 30 mg daily, 23·6% of men and 28·1% of women have intakes less than 20 mg daily, and 4·7% of men and 3% of women have intakes less than 10 mg daily. These percentages increase during the winter. A moderate correlation is present between vitamin C intake and L.A.A. level. L.A.A. levels increase in parallel with but lag behind seasonal increases in vitamin C intake.